SYMBOLIC INTERACTION ON INDIGENIOUS PEOPLE OF MANGGARAI, FLORES NTT (A Study on Local Wisdom of Penti Ceremony in the Context of Environment Preservation - Niman, Erna Mena (Institut Seni Indonesia Surakarta, 2022)
The problem of forest destruction really needs wise efforts of conservation. One of the efforts is to make use of society’s local wisdom. This study aims at examining the meaning, and values contained in the Manggarain Penti cultural ceremony in the context of forest conservation. To reach the objectives in question, interview, observation, and documentation were used to collect data which were subsequently interpreted following symbolic interaction theory. Findings revealed that aside from as a pillar of conservation, Penti also has several meanings, namely pillar of spiritual life (gratitude and request), forum for togetherness, a behavior controller, and as a means of self-recovery /repentance. Meanwhile, based on the meaning given, in addition to ecological value, Penti also has religious value and social value. Thus, penti is concerned with eco-socio- telogy Manggaraian conception toward the existence of nature.